Dictionary of christian words: setting up the list of entries - Dobrushina Ekaterina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The paper discusses the issues of compiling the entry list for the Encyclopaedic Dictionary of Russian Christian Words. It presents a fragment of the classifi cation of the terminology in the domain and suggests to use the frequency of a lexical item in relevant texts as a criterion of its terminologization. The paper also considers whether proper names should be included in the Dictionary.